The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1007/s40725-023-00208-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights

Leen Depauw,
Emiel De Lombaerde,
Els Dhiedt
et al.

Abstract: Purpose of Review International ambitions for massive afforestation and restoration are high. To make these investments sustainable and resilient under future climate change, science is calling for a shift from planting monocultures to mixed forests. But what is the scientific basis for promoting diverse plantations, and what is the feasibility of their establishment and management? As the largest global network of tree diversity experiments, TreeDivNet is uniquely positioned to answer these pressing questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 183 publications
0
0
0
Order By: Relevance
“…Despite attempts using structural equation models (SEMs) to identify direct and indirect relationships (Chen et al, 2018; Chen et al, 2023; Li et al, 2020), mechanistically disentangling these drivers remains challenging in observational studies. Planted tree diversity experiments, which were specifically designed to compare monocultures and mixtures of increasing diversity while controlling for environmental variation (Depauw et al, 2024; Scherer-Lorenzen et al, 2005), offer an ideal setting for elucidating linkages among C stocks and fluxes. Until recently, the young age of most tree diversity experiments, the slow development of trees in boreal and temperate experiments and the different response times and dynamics of C compartments over the course of stand development (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite attempts using structural equation models (SEMs) to identify direct and indirect relationships (Chen et al, 2018; Chen et al, 2023; Li et al, 2020), mechanistically disentangling these drivers remains challenging in observational studies. Planted tree diversity experiments, which were specifically designed to compare monocultures and mixtures of increasing diversity while controlling for environmental variation (Depauw et al, 2024; Scherer-Lorenzen et al, 2005), offer an ideal setting for elucidating linkages among C stocks and fluxes. Until recently, the young age of most tree diversity experiments, the slow development of trees in boreal and temperate experiments and the different response times and dynamics of C compartments over the course of stand development (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and observational studies have increasingly demonstrated a positive relationship between the provision of forest ecosystem functions and services and biodiversity (Gamfeldt et al, 2013; Huang et al, 2018; Liang et al, 2016; Veryard et al, 2023; Gao et al, 2021). Specifically, the planting of mixed-species forests (Messier et al, 2021; Puettmann et al, 2009) can achieve higher biomass productivity in restoration projects, as diverse plantations have been shown to be more productive than monocultures (Depauw et al, 2024; Fichtner et al 2018). The mechanisms that drive these biodiversity-productivity relationships (BPRs) in forests are, however, still under debate.…”
Section: Introductionmentioning
confidence: 99%